The Role of Teachers in Application of Learning Theory Constructivism in Schools - Rosana, Dina Syarifah; Handayaningrum, Warih (Berpusi Publishing, 2024)
Constructivism is a psychology and philosophical perspective that argue that individuals form or construct much of their learning and understanding. In recent years, constructivism theory has increasingly been applied in the learning process. A number ofeducation experts argue that rather than talking about how knowledge is obtained, it is more important to discuss how that knowledge is built. Even though there are several experts who have different opinions on the factors that influence learning and cognitive processes in students, their theoretical perspectives agree in defining constructivism theory. On the one hand, teachers are responsible for the learning process in the classroom. As a teacher, the teachers is tasked with designing learning programs,implementing and conducting assessments. Note only that, teachers must also be capable to create, build, discuss, collaborate andcarry out experiments in a learning activity. Therefore, this article will discuss constructivism theory and its applications in thelearning process using constructivist principles.